Combinations of dual-function azide-containing crosslinkers with C-H insertion capabilities for polymeric elastomers with improved adhesion properties. (5th January 2022) - Jung, Dong Wook; Hong, Sung Chul
Graphical abstract: Highlights: Clean fabrication of elastomer with improved adhesion capability is proposed. A combination of dual-function azide-containing crosslinkers is attempted. Noncatalytic C-H insertion capabilities of azide groups are utilized. Triethoxysilane group affords adhesion capability on OH-containing substrates. Abstract: The utilization of the noncatalytic C-H insertion capability of the nitrene intermediate of azide-containing compounds is proposed in this study for the clean fabrication of polymer-inorganic functional hybrid materials with elasticity and adhesion capabilities. For this purpose, a combination of dual-function azide-based crosslinkers composed of azidosilane (6-azidosulfonylhexyltriethoxysilane, AS) and diazide-based crosslinkers [tri(ethylene glycol)diazidoformate, GDAF] is attempted. AS affords good adhesion capability of polymer materials to OH-containing inorganic substrate/fillers, while GDAF undergoes a simultaneous C-H insertion reaction with polymer chains in bulk, affording enough crosslinking sites to improve elasticity. Through adjustments of the compositions and curing conditions, the styrene butadiene rubber compound with the proposed combination of crosslinkers exhibits good mechanical properties and excellent elasticity, as demonstrated by the low tension set value. The compound also exhibits improved adhesion capability on OH-containing silica, quartz and polyimide films, providing functional hybrid materials with an ideal combination of elasticity and adhesion capabilities suitable possibly for cutting-edge applications.